BIBLIOMETRIC ANALYSIS OF ELEMENTARY SCHOOL STUDENTS' CRITICAL THINKING SKILLS IN 2021-2025 - Cahyani, Fayza Arum; Hidayah, Nurul; Ningrum, Ayu Reza (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
Critical thinking skills in elementary school students are something that must be developed, because it will make students able to think logically. Practicing critical thinking will have an impact on analyzing a problem that exists around them. The purpose of this study was to examine the development of research on the critical thinking skills of elementary school students with a Qualitative approach to the Computational Bibliometric analysis method using Vosviewer. Data were collected with Publish or Perish from the Google Scholar database with a range of 2021 to 2025 as many as 1,000 journals. The results of the study showed that research on critical thinking of elementary school students has increased every year. Recent research tends to examine more innovative and contextual learning approaches, such as project-based and inquiry-based learning, for students' critical thinking skills. Recent research also focuses more on developing critical thinking skills to be integrated into the applicable curriculum, including the independent curriculum. Research on the critical thinking skills of elementary school students has grown rapidly in the last five years, but those related to computational thinking, inquiry, and independent curriculum are still little discussed so that they can be opportunities for further research